Formation of an electron beam by an electron-optical system using a composite field emitter made of thermally expanded graphite and a mixture of thermally expanded graphite with diamond granules - Taradaev Evgeny; Sominskii Gennadii; Taradaev Sergei; Gordeev Sergey (St. Petersburg Polytechnical University Journal: Physics and Mathematics)
In the paper, the characteristics of electron flows formed by an electron-optical system with composite field emitters, made from thermally expanded graphite or a mixture of such graphite with diamond granules have been studied. These cathodes were developed at the Saint Petersburg Polytechnic University and the Central Research Institute of Materials. A distinguishing feature of these cathodes is their improved geometry. The maximum achievable emission currents, as well as the longitudinal and transverse components of the velocity of emitted electrons in the electron flow, were determined. The measurements were carried out in pulsed and continuous operations. Experiments showed that these types of cathodes provided emission currents up to 30 mA and operated stably under technical vacuum conditions.